The Role of Qanun in the Implementation of Islamic Family Law in Sharia-Based Countries: Challenges and Opportunities - Fadhilah Fadhilah (Journal of Nafaqah, 2024)
This study aims to explore the role of qanun in the implementation of Islamic family law in sharia-based countries, as well as identify the associated challenges and opportunities. Qualitative research methods were used by conducting in-depth interviews with relevant stakeholders, analysis of legal documents, and direct observation of the implementation process of Islamic family law through qanun. The results showed that qanun has an important role as a local legal instrument that reflects the values, norms, and demands of the community. However, qanun implementation is also faced with a number of challenges, including incompatibility with human rights standards and differences in interpretation between religious authorities and positive law. Nonetheless, there are opportunities to improve the implementation of Islamic family law through qanun, such as updating qanun to ensure fairness and protection of individual rights, and increasing dialogue between various stakeholders. The implication of this study is the need for reform and capacity building of local legal institutions to implement qanun more effectively and fairly. Policy recommendations include the revision of qanuns that are inconsistent with human rights principles, the implementation of training for stakeholders on Islamic family law, and the strengthening of monitoring and enforcement mechanisms. This research provides an in-depth understanding of the complexities of implementing Islamic family law through qanuns in sharia-based countries, and provides a foundation for future improvements in legal policy and practice.